2017
DOI: 10.1364/oe.25.027104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of sub-diffraction quasi-non-diffracting beams by angular spectrum compression

Abstract: Quasi-non-diffracting beams are attractive for various applications, including optical manipulation, super-resolution microscopes, and materials processing. However, it is a great challenge to design and generate super-long quasi-non-diffracting beams with sub-diffraction and sub-wavelength size. In this paper, a method based on the idea of compressing a normalized angular spectrum is developed, which makes it possible and provides a practical tool for the design of a quasi-non-diffracting beam with super-osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…In the past several years, various types of superoscillatory lenses have been demonstrated, including linear‐focusing lenses, [ 18,19 ] spot‐focusing lenses, [ 20,21 ] long‐depth‐of‐focusing lenses, [ 22–24 ] and vector wave superoscillatory lenses. [ 25–30 ] So far, the smallest PSF that has ever been experimentally demonstrated has a full‐width‐at‐half‐maximum (FWHM) value of 0.33λ, [ 31 ] where λ is the working wavelength. Due to their comparative large sidelobes, those super‐resolution lenses are not suitable for direct imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several years, various types of superoscillatory lenses have been demonstrated, including linear‐focusing lenses, [ 18,19 ] spot‐focusing lenses, [ 20,21 ] long‐depth‐of‐focusing lenses, [ 22–24 ] and vector wave superoscillatory lenses. [ 25–30 ] So far, the smallest PSF that has ever been experimentally demonstrated has a full‐width‐at‐half‐maximum (FWHM) value of 0.33λ, [ 31 ] where λ is the working wavelength. Due to their comparative large sidelobes, those super‐resolution lenses are not suitable for direct imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In a later study, surprisingly, classical binary Fresnel zone plates were used to generate subdiffraction optical needles for multiple polarizations via optimization-free design 130 . A numerical simulation showed that, compared to the optical needle reported in reference 129 , those that were created by classical Fresnel zone plates have smaller fluctuations in optical intensity along the optical axis. The experimental results showed that the transverse sizes and the axial lengths were 0.40λ–0.54λ and 90λ, 0.43λ–0.54λ and 73λ and 0.34λ–0.41λ and 80λ for the generated optical needles with circular, longitudinal and azimuthal polarizations, respectively, as shown in Fig.…”
Section: Superoscillatory Optical Devicesmentioning
confidence: 82%
“…The value of the wavelength λ is determined by several parameters, including the lens radius, the working wavelength λ 0 , the focal length and the optical needle propagation distance. The extension of an optical needle in water 124,129 can be explained similarly. Interestingly, utilizing the same strategy, subdiffraction diffractionless beams can be created with the same transverse size and propagation distance but lower intensity fluctuations along the optical axis using a classical Fresnel zone plate, which is entirely free from optimization and allows one to design subdiffraction diffractionless beams for multiple polarizations using very simple algebra 130 , as shown in Fig.…”
Section: Design Methodsmentioning
confidence: 99%
See 2 more Smart Citations